Microphysicalism and the scope of the zombie argument - Bernal Velásquez, Reinaldo José (Estudios de Filosofía, 2019)
Chalmers’ (1996) zombie argument against physicalism (or ‘materialism’) about (phenomenal) consciousness supposes that every property of a composed physical system supervenes (logically) on the system’s fundamental constituents. In this paper, I discuss the significance of this supposition and I show that the philosophy of physics provides good grounds to resist it. As a result, I conclude that the zombie argument does not rule out a physicalist view of consciousness that conceives it as emergent in the sense of S-emergence (Howard, 2007). I finish by discussing some objections.